2021
DOI: 10.1186/s13006-021-00438-5
|View full text |Cite
|
Sign up to set email alerts
|

“Fear of stopping” vs “wanting to get off the medication”: exploring women’s experiences of using domperidone as a galactagogue - a qualitative study

Abstract: Background Domperidone is the most frequently prescribed medicine used to increase breast milk supply. There is considerable controversy surrounding the use of domperidone in lactation, due to limited evidence about efficacy and concerns about rare but life-threatening side-effects. Despite this, in many high-income settings such as Australia, use of domperidone among breastfeeding mothers appears to be increasing. The aim of this paper was to explore women’s experiences of using domperidone du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In contrast, participants perceived GPs as the most unhelpful sources of information regarding galactagogues. This finding is consistent with that of other researchers, where GPs were observed to have less current knowledge and specific training in breastfeeding support in general (Cramer et al, 2021; Holtzman & Usherwood, 2018), or related to the use of specific galactagogues (e.g., domperidone; Zizzo, Rumbold et al, 2021). A perceived lack of helpfulness may be related to breastfeeding support in general, a lack of information provided about the use of specific galactagogues, receipt of conflicting advice, or the provision of advice considered too generalized or inappropriate for an individual’s situation.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, participants perceived GPs as the most unhelpful sources of information regarding galactagogues. This finding is consistent with that of other researchers, where GPs were observed to have less current knowledge and specific training in breastfeeding support in general (Cramer et al, 2021; Holtzman & Usherwood, 2018), or related to the use of specific galactagogues (e.g., domperidone; Zizzo, Rumbold et al, 2021). A perceived lack of helpfulness may be related to breastfeeding support in general, a lack of information provided about the use of specific galactagogues, receipt of conflicting advice, or the provision of advice considered too generalized or inappropriate for an individual’s situation.…”
Section: Discussionsupporting
confidence: 92%
“…Even with these concerns about potential cardiac side effects, domperidone was still largely perceived as safe by women in this survey, which may demonstrate that these concerns for cardiac safety are not being communicated or that the perceived benefits outweigh the risks. This is supported by evidence from a qualitative study on a subset of women from this survey which found that galactagogue use is often underpinned by a strong determination to breastfeed, often resulting in women preferencing the potential benefits to their infant over potential risks to themselves [22,24].…”
Section: Discussionmentioning
confidence: 58%
“…This is reflected in the most recent guidelines from the Academy of Breastfeeding Medicine that, while stating domperidone may increase breast milk supply, do not provide any direct practice recommendations regarding optimal dosing regimens and treatment approaches [10]. This may lead to inconsistent prescribing practices and broad variations in dosing and duration of use [10,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential side effects and contraindications associated with pharmacological galactagogues have raised concerns among healthcare professionals and patients. These issues include possible central nervous system side effects, cardiac arrhythmias, and drug interactions, posing risks to both the mother and infant (18,19). Therefore, there is a growing need to explore alternative solutions, particularly herbal galactagogues, which are considered safer and more natural options for promoting lactation (20,21).…”
Section: Introductionmentioning
confidence: 99%